Development of an Innovative ADDIE-Based Islamic Education Curriculum Model in Madrasah Aliyah Negeri - Mariani Mariani; Jamaluddin Idris; Silahuddin Silahuddin; Nurmahni Harahap; Maria Ulfa; Nazarullah Nazarullah (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The development of an innovative Islamic Education (PAI) curriculum has become an urgent need in responding to the challenges of 21st-century learning, particularly in state Islamic senior high schools that are required to integrate Islamic values, technology, and character education. This study aims to develop an innovative ADDIE-based Islamic Education curriculum development model for teachers in Innovative State Islamic Senior High Schools (Madrasah Aliyah Negeri) in Aceh Province. This research employed a mixed-methods approach by combining qualitative and quantitative data. Qualitative data were collected through observations, interviews, and documentation, while quantitative data were obtained through expert validation and teacher practicality tests. The needs analysis revealed a significant gap between the ideal curriculum design and classroom practices, especially in terms of instructional innovation, technology integration, and character strengthening. The design and development stages resulted in an innovative Islamic Education curriculum module that is student-centered, integrative, contextual, and grounded in Islamic values. Expert validation results indicated a very high level of feasibility, with average scores ranging from 91% to 93% across content, language, and graphical aspects. The implementation of the model in three madrasahs demonstrated its effectiveness in enhancing teachers’ creativity, increasing students’ learning motivation, and improving the relevance of learning materials to real-life contexts. This study concludes that the ADDIE-based Islamic Education curriculum model is valid, practical, and effective. The findings imply that the model can be scaled up through systematic professional development programs for Islamic Education teachers and supported by educational policies that promote curriculum innovation grounded in Islamic values.